Cryptococcal infections in two patients receiving ibrutinib therapy for chronic lymphocytic leukemia. (April 2019) - Stankowicz, Matthew; Banaszynski, Megan; Crawford, Russell
Cryptococcal infections are responsible for significant morbidity and mortality in immunocompromised patients. Reports of these infections in patients on small molecular kinase inhibitors have not been widely reported in clinical trials. We describe one case of cryptococcal meningoencephalitis and one case of cryptococcal pneumonia in two patients who were receiving ibrutinib for chronic lymphocytic leukemia. Despite different sites of cryptococcal infection, both patients had similar presentations of acute illness. Patient 1 was worked up for health care–associated pneumonia, as well as acute sinusitis prior to the diagnosis of cryptococcal meningoencephalitis. He also had a more complex past medical history than patient 2. Patient 2 developed atrial fibrillation from ibrutinib prior to admission for presumed health care–associated pneumonia. Cryptococcal antigen testing was done sooner in this patient due to patient receiving high-dose steroids for the treatment of underlying hemolytic anemia. We conclude that patients who develop acute illness while receiving ibrutinib should be considered for cryptococcal antigen testing.